Investigation of structure, mechanical and tribological properties of short carbon fiber reinforced UHMWPE-matrix composites. (July 2015) - Chukov, D.I.; Stepashkin, A.A.; Maksimkin, A.V.; Tcherdyntsev, V.V.; Kaloshkin, S.D.; Kuskov, K.V.; Bugakov, V.I.
Abstract: Structural, mechanical and tribological properties of composite materials based on ultra-high molecular weight polyethylene reinforced with carbon fibers were investigated. The effect of surface modification of carbon fibers on the interaction at the fiber–matrix interface in UHMWPE based composites was studied. It was found that the thermal oxidation of carbon fibers by air oxygen at 500 °C can significantly enhance the interfacial interaction between the polymer matrix and carbon fibers. This allowed us to form composite materials with improved mechanical and tribological properties.